2010
DOI: 10.1152/ajpcell.00173.2010
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide promotes angiogenesis via AMP-activated protein kinase

Abstract: Ischemia induces angiogenesis as a compensatory response. Although ischemia is known to causes synthesis and release of calcitonin gene-related peptide (CGRP), it is not clear whether CGRP regulates angiogenesis under ischemia and how does it function. Thus we investigated the role of CGRP in angiogenesis and the involved mechanisms. We found that CGRP level was increased in the rat hindlimb ischemic tissue. The expression of exogenous CGRP by adenovirus vectors enhanced blood flow recovery and increased capil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 40 publications
(39 reference statements)
3
69
0
Order By: Relevance
“…It was revealed that apelin is expressed in vascular endothelial cells and participates in regulating their proliferation and regenerative angiogenesis (22,23,24). Calcitonin gene-related peptide and vascular endothelial growth factor were reported to promote angiogenesis by promoting AMPK and Akt signaling activation, respectively (25,26). AMPK and Akt directly phosphorylate eNOS (17,27), which is important in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that apelin is expressed in vascular endothelial cells and participates in regulating their proliferation and regenerative angiogenesis (22,23,24). Calcitonin gene-related peptide and vascular endothelial growth factor were reported to promote angiogenesis by promoting AMPK and Akt signaling activation, respectively (25,26). AMPK and Akt directly phosphorylate eNOS (17,27), which is important in angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing intracellular cAMP and calcium leads to changes in cell morphology and function [42,43] , but the effect of cAMP signaling on CGRP-dependent BMP-2 expression remains unclear. To examine these events, we examined the synthesis of BMP-2 mRNA and protein after pretreatment with the cAMP pathway inhibitor H-89.…”
Section: Discussionmentioning
confidence: 99%
“…Major sources of ROS are thought to be eNOS-uncoupling and NADPH oxidase [41] CGRP has been shown to activate eNOS via the cAMP-PKA [42] and AMPK [43] pathways.…”
Section: Discussionmentioning
confidence: 99%